Assessment of adverse events and patient safety culture in dental practice: cross-sectional study - Fabrícia Paola Fernandes Ribeiro DOS SANTOS; Débora Dupas Gonçalves DO NASCIMENTO; Inara Pereira da CUNHA (Universidade Estadual Paulista, 2024)
Abstract Introduction Adverse events (AE) are injuries or harm not related to the natural progression of the disease but that result in harm to patients. In healthcare institutions, the adoption of a patient safety culture can reduce the occurrence of AE. Objective To identify the frequency of AE reported by dentists in primary dental care and analyze the dimensions of patient safety culture (PSC) associated with this outcome. Material and method This cross-sectional study was conducted in two Brazilian states in 2021. A total of 350 dentists working in primary dental care participated in the study. The outcome (AE) was measured using a semi-structured questionnaire, which was tested through a pilot study. Independent variables were collected through sociodemographic questionnaires and the validated Medical Office Survey on Patient Safety Culture instrument, which measures dimensions of PSC. Poisson regression analysis was used. Result The most reported event was: "The patient required an urgent return visit due to pain, swelling, or other reasons" after a clinical intervention (60.6%). The dimensions of PSC related to AE were "Overall perception of patient safety and quality" (PR: 0.86, 95% CI: 0.76-0.89), "Work processes and standardization" (PR: 0.86, 95% CI: 0.78-0.92), and "Teamwork" (PR: 1.11, 95% CI: 1.03-1.73). Conclusion Adverse events are frequent in primary dental care practice and are associated with dimensions of patient safety culture. This reinforces the need to expand knowledge about this topic and implement barriers to prevent harm to patients during dental care at this level of health care.